Re-examination of Two Zero Texture of Neutrino Mass Matrix After Neutrino-2012 - Phong, Nguyen Thanh (Communications in Physics, 2013)
We re-study the seven neutrino mass matrices with two independent vanishing entries under the latest results of neutrino oscillation experiments after the neutrino - 2012 conference. It is shown that the pattern B 1 could be excluded since this pattern realizes very small value of mixing angle theta13. The remain six textures satisfy the current experimental data. We also find that all seven textures of neutrino mass matrix possess the normal hierarchy of neutrino mass spectrum.